ANALISIS MANAJEMEN RISIKO OPERASIONAL PADA UMKM FOTOCOPY “MENCIRIM INDAH PHOTO” MEDAN SUNGGAL - Lelly Yowana Lase; Seni Krisdayanti Putri Halawa; Syahfia Siregar; Tuti Handayani Zebua; Ayunda Fatmasari (Journal of Innovative and Creativity (Joecy), 2026)
Focus - This study focuses on identifying and mapping operational risks at a photocopy, printing, and laminating MSME, Mencirim Indah Photo in Medan Sunggal, using the 5M Framework approach combined with a risk register instrument. Objective - This study aims to identify the operational risks faced by Mencirim Indah Photo in its daily business operations, measure the level of these risks through likelihood and impact analysis, trace the root causes based on five dimensions (Man, Machine, Material, Method, Money), and formulate mitigation strategies as well as Standard Operating Procedures (SOPs) to serve as practical guidelines for risk management. Method - The research employed a descriptive qualitative approach within the framework of community service activities. Data were collected through direct on-site observation, in-depth interviews with the owner and employees, and documentation comprising written records and photographs. The collected data were analyzed using the 5M framework to identify sources of risk, followed by an assessment of severity levels via a risk register, resulting in risk scores and classifications (Low, Medium, High, Extreme). Findings - The study identified six key operational risks; two were classified as "High" with the highest scores (photocopier malfunction and damp paper, each scoring 15), while three others were categorized as "Medium." Based on these findings, management strategies (mitigation, transfer, acceptance, and avoidance) and concrete action plans were developed, alongside Standard Operating Procedures (SOPs) for photocopier maintenance and paper storage, serving as practical guidelines to prevent the recurrence of operational disruptions.